PENYELESAIAN SENGKETA MELALUI UPAYA ADMINISTRATIF DI PENGADILAN TATA USAHA NEGARA PADANG - Bayu Rahmaddoni; Kurnia Warman; Yuslim Yuslim (Program Magister Ilmu Hukum Universitas Ekasakti, 2023)
This paper examines the legal certainty of state administrative dispute resolution in taking governmental measures. How is the existence of administrative efforts? What is the judge's legal consideration of not carrying out administrative effort? The results of this study indicate that administrative efforts must be made consisting of administrative objections and appeals unless otherwise stipulated by a law. Based on the judge's legal considerations regarding state administration disputes that do not and/or take administrative measures but are not in accordance with the provisions of Law Number 30 of 2014 concerning Government Administration juncto Supreme Court Regulation Number 6 of 2018 concerning Guidelines for the Settlement of Government Administrative Disputes After Taking Administrative Efforts then the lawsuit is declared not accepted (niet ontvankelijkverklraad).